Epidemiological profile of COVID-19 patients undergoing invasive mechanical ventilation in a Brazilian public hospital: a comparison between 2020 and 2021 - Oliveira, Kelly Cristina da Silva; Limongi, Vivian; Aily, Jessica Bianca; Souza Júnior, José Eustáquio de; Oioli, Ana Paula Toma; Amaral, Carolina de (Revista Prevenção de Infecção e Saúde, 2023)
Introduction: COVID-19 can lead to respiratory complications and require some patients to undergo invasive mechanical ventilation. As a recent disease, it is not clear which patient characteristics predispose to the need for the procedure. Aim: The aim of this study was to describe and compare the epidemiological profile of patients who required invasive mechanical ventilation between 2020 and 2021. Outlining: This is a descriptive and analytical study. Patient characteristics and outcomes were collected from medical records and divided into four groups (survivors - GS and non-survivors - GN of 2020 and 2021). Results: The sample consisted of 501 patients over 18 years of age. There was a difference (p<0.005) in Chronic Obstructive Pulmonary Disease, pneumothorax, age, prone position, and dialysissupport in the GN, and tracheostomy, longer hospital stays, and longer stay in the Intensive Care Unit in the GS. The year 2020 had an older population with pneumothorax and neurological disease among non-survivors. Implications: The findings of the study will assist in the management of healthcare resources, implementation of measures to reduce the time of mechanical ventilation, and prioritization of vaccination for at-risk groups.